DEVELOPMENT OF MOBILE LEARNING BASED- INTERACTIVE MULTIMEDIA IN PROGRAMMING LANGUAGE CLASS AT STAIN BATUSANGKAR - Lita Sari Muchlis; Fitra Kasma Putra (Ta'dib, 2017)
This study aims at developing mobile learning-based interactive media in programming language I subject. This research uses the ADDIE model, in which the proposed instructional media are tested to students of Informatics Management study program at STAIN Batusangkar, particularly in Programming Language course I. Data collection was done by distributing the questionnaires. At first, the need analysis was conducted by observing the related phenomena and previous research. Next, after the designing stage, the product was validated by three experts. As the result, the product, in terms of content, was 81,05 categorised very valid, besides in terms of design, it was valid with 85,6 score. In terms of practicality, the product was applied to the students. The result shows that the product was practical to use in Progamming Language course I. In order to find out its effectivity, the product was tested twice, before and after treatment. The mean score of post-test result was higher t “test” 0,001<0,05 than that of the pre-rest. Based on data analysis both design validation by experts and test results of the students, then the interactive online learning media is recommended to be developed for STAIN Batusangkar students.